Changes in the T-cell receptor Vβ gene repertoire after allogeneic hematopoietic stem cell transplantation - 刘启发 李扬秋 杨冬 张钰 杨力建 陈少华 孙竞 刘晓力 周淑芸 (Chinese medical journal, 2004)
Background We distinguished graft-versus-host disease (GVHD) from graft-versus-leukemia (GVL) effects and to investigate the distribution of T-cell receptor (TCR) Vβ gene repertoire in individuals with leukemia before and after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods Peripheral blood mononuclear cells (PBMC) were obtained from 10 normal individuals, 8 donors and 11 patients with leukemia before and after transplantation. Polymerase chain reaction (PCR) amplification of complementarity-determining region 3 (CDR3) of 24 TCR Vβ genes was used to examine serial samples of PBMC. The PCR products were further analyzed by genescan to evaluate clonality of T cells. Results The 24 TCR Vβ gene repertoire displayed highly diverse and polyclonal spectratypes in all normal individuals and 4 of 8 donors. Another 4 donors expressed part of the 24 TCR V~ subfamily and 1 donor had oligoclonality. The expressions of the 24 TCR V~ subfamilies were skewed and restricted in 11 leukemia patients before and after transplantation. Some absences of 24 TCR Vβ subfamily expression were quite similar between the recipients pro-transplantation and related donors. The number of subfamilies expressed increased over time post-transplantation, but the restricted expressions of the subfamily could last 6-30 months after transplantation. All patients with GVHD and some without GVHD exhibited T cell clonal expansion. The expansive T cell clone was distributed in Vβ 2-3, 16-17, 18-19, 21 and Vβ 23 in patients with GVHD and in Vβ 7, 9, 16 and 19 in patients without GVHD. One patient with syngeneic-HSCT (syn-HSCT) had Vβ 15 and 16 T cell expansion after transplantation. One patient displayed Vβ 18 T cell expansion after donor lymphocyte infusion (DLI). Conclusions Normal individuals express the entire 24 TCR Vβ gene repertoire and have polyclonal distribution. However, the TCR Vβ gene repertoire is only partially expressed in some donors. The TCR Vβ gene repertoire is restrictedly expressed in a skew fashion in patients with leukemia before and after transplantation. The number of TCR Vβ gene subfamilies increases over time posttransplantation. GVHD and GVL effects may induce the proliferation of T cell clones. Clinical GVL response may be distinguished from GVHD alloreactivity through the host MHC antigen.